Hubungan Dukungan Keluarga dengan Tingkat Kecemasan Pasien Pre-Operasi Bedah Mayor di RS Bhakti Asih Kota Tangerang - Heni Fitriani; Ekberth Mandaku; Tanto Tanto; Dalva Gumilar (Institut Nalanda, 2025)
Anxiety in pre-operative major surgery patients is a common occurrence and can affect the post-operative healing process. Family support plays an im- portant role in reducing this anxiety, as it provides a sense of security and comfort. This study aims to examine the relationship between family support and anxiety levels in pre-operative major surgery patients at RS Bhakti Asih, Tangerang City. This research uses a quantitative design with a correlational approach and a cross- sectional study design. The sample consists of 78 patients undergoing major sur- gery at RSU Bhakti Asih who met the inclusion criteria, selected using nonproba- bility sampling with a purposive sampling technique. Data were collected using two instruments: a family support questionnaire and the Zung Self-Rating Anxiety Scale. Data analysis was conducted using the Chi-Square test. The results showed that the majority of respondents received high family support, with 31 respondents (39.7%), and the most dominant anxiety level among patients was categorized as normal/not anxious, with 23 respondents (29.5%). The Chi-Square test analysis yielded a p-value of 0.000 < 0.05. It can be concluded that the study demonstrates a significant relationship between family support and anxiety levels in pre-opera- tive patients.